COFFEE: control‐free noninvasive fetal chromosomal examination using maternal plasma DNA. (17th February 2017) - Sun, Kun; Chan, K. C. Allen; Hudecova, Irena; Chiu, Rossa W. K.; Lo, Y. M. Dennis; Jiang, Peiyong
Abstract: Objective: The aim of this study is to develop an approach for analyzing plasma DNA sequencing data for noninvasive fetal chromosomal aneuploidy testing that does not require the comparison with control samples or a series of selected genomic regions. Results: We developed the control‐free noninvasive fetal chromosomal examination (COFFEE) algorithm by utilizing the size differences between the fetally derived and maternally derived DNA molecules in maternal plasma. We applied COFFEE on three datasets generated in different experimental settings. COFFEE showed 100% accuracy in trisomy 21 testing on these datasets. In contrast, samples analyzed using an existing control‐based z ‐score method would introduce a false‐positive result because of batch‐to‐batch variation, when the tested samples were analyzed using control samples from other batches. We believe that COFFEE is useful for enhancing the cost‐effectiveness of noninvasive fetal chromosomal aneuploidy testing particularly in laboratories with small caseloads. Source code and testing datasets for COFFEE are available for download athttp://www.cuhk.edu.hk/med/cpy/Research/COFFEE/ . Conclusion: Control‐free noninvasive fetal chromosomal examination is demonstrated to be a versatile data analysis approach and could enhance the application of noninvasive fetal chromosomal aneuploidy detection. © 2017 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Noninvasive prenatal testing for fetal aneuploidies has been rapidly adopted in clinical practice and is largely based on the principle of counting DNA molecules in maternal plasma. Most protocols require the establishment of reference values from the testing of control samples. Fetally derived DNA molecules have been demonstrated to be shorter than maternally derived ones, providing an opportunity to develop size‐based approaches for the detection of fetal chromosomal aneuploidies. Both analyses generally require control samples. What Does This Study Add? We have developed a novel approach for fetal aneuploidy testing, named control‐free noninvasive fetal chromosomal examination. It obviates the need for the use of control data, enabling platform‐independent analysis.